Altered distribution, activation and increased IL-17 production of mucosal-associated invariant T cells in patients with acute respiratory distress syndrome. Issue 9 (27th January 2022) - Kim, Tae-Ok; Park, Ki-Jeong; Cho, Young-Nan; Jin, Hye-Mi; Jo, Young-Goun; Kim, Hyo Shin; Ju, Jae Kyun; Shin, Hong-Joon; Kho, Bo-Gun; Kee, Seung-Jung; Park, Yong-Wook
Abstract : Objective: Mucosal-associated invariant T (MAIT) cells are a subset of innate-like T cells that are engaged in a number of diseases, but their roles in acute respiratory distress syndrome (ARDS) are not fully examined yet. This study aimed to examine levels and functions of MAIT cells in patients with ARDS. Methods: Peripheral blood samples from patients with ARDS (n=50) and healthy controls (HCs, n=50) were collected. Levels of MAIT cells, cytokines, CD69, programmed cell death-1 (PD-1) and lymphocyte-activation gene 3 (LAG-3) were measured by flow cytometry. Results: Circulating MAIT cell levels were significantly reduced in patients with ARDS than in HCs. MAIT cell levels were inversely correlated with disease severity and mortality. Cytokine production profiles in MAIT cells showed that percentages of interleukin (IL)-17 producing MAIT cell were significantly higher in patients with ARDS than in HCs. Patients with ARDS exhibited higher expression levels of CD69, PD-1 and LAG-3 in circulating MAIT cells. Moreover, levels of MAIT cells and expression levels of CD69, PD-1 and IL-17 in MAIT cells were higher in bronchoalveolar lavage fluid samples than in peripheral blood samples. Our in vitro experiments showed that MAIT cells triggered macrophages to produce proinflammatory cytokines such as tumour necrosis factor-α, IL-1β and IL-8. Conclusions: This study demonstrates that circulating MAIT cells are numerically deficient in patients with ARDS. In addition, MAIT cells were found to be activated, migrate into lung, secrete IL-17 and then stimulate macrophages. These findings suggest that MAIT cells contribute to the worsening of inflammation in the lung of patients with ARDS.